Analsisis Risiko Operasional Berbasis Pendekatan Enterprise Risk Management pada Rumah Makan Erna Lubuk Pakam - Feby Andina; Ciptaning Alifadiba; Shania Karibna Br Bangun (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The development of the restaurant business is currently quite existent in Indonesia. However, every business cannot be separated from any threats that may arise in the future. Business risk is a series of risks that may be associated with every business activity carried out. This research uses a qualitative approach, where data is collected through various techniques. The data collection techniques used are observation and interviews with Erna's Restaurant. In addition to using qualitative research methods with interviews and other data collection techniques, this research also utilizes the Enterprise Risk Management (ERM) approach in its analysis by conducting risk identification and risk assessment. The results showed that the recommended control measures include strengthening employee supervision, evaluating the production process, cooking quality standards, employee training, reward and punishment systems, and focusing on customer satisfaction. It is expected that with the implementation of these solutions, Erna's Restaurant can manage operational risks effectively and improve its business performance. Proper risk management is very important to minimize company losses due to operational risks.